DSc. Juan Amado Díaz Sarduy: founder of the Medicine School of Oriente University - María Antonia Peña Sánchez; José Daniel Pascual Díaz; María Victoria Miyares Peña (Centro Provincial de Información de Ciencias Médicas, 2022)
With this work it is hoped to rescue part of Dr. Juan Amado Díaz Sarduy fruitful and long life, associate and merit professor, besides his honorary doctorate degree of the University of Medical Sciences in Santiago de Cuba. The text is a tribute to such famous doctor, upright revolutionary and true mentor of Imaging in this province. His recent death, on March 28, 2022, leaves a deep feeling of sadness in those that knew him; but his example remains, always in the first line of all battles, and the everlasting memories of his spiritual nobility, fidelity to his friends and love to his family.